Retrospective analysis of infection-related deaths of sudden unexpected death in infancy cases at Salt River Mortuary - Matlebjane, Sefule Anastacia (Department of Clinical Laboratory Sciences, 2023)
Sudden unexpected death in infancy (SUDI) remains a global concern and is a particular burden in South Africa. Infections have been previously linked to SUDI deaths, but empirical data in a South African context is lacking. This study aimed to explore the burden and risk factors of infection-related infant death at Salt River Mortuary (SRM). To identify the types of infections associated with SUDI in a local setting, medico-legal files from SRM between 1 January 2017 and 31 December 2018 were reviewed. Included cases involved infants between 1 day and 365 days old where an infectious cause of death was either suspected or confirmed (n=288). Variables pertaining to cause of death, scope of post-mortem investigation, clinical history and risk factors were collected from case files and assessed. Most infants (73.6%) demised within four months of age. The major modifiable risk factors were cosleeping (95.0%, n=264/278), side or prone sleeping position of the infant (73.3%, n=195/266), as well as tobacco smoke exposure (46.9%, n=122/260). Respiratory infection was the leading cause of death in this population, followed by gastroenteritis. Philippi area recorded the most gastroenteritis and respiratory infection-related deaths at 25.0% (n= 8/32) and 23.4% (n= 45/192), respectively. Milnerton and Gugulethu recorded 18.8% (n=6/32) and 15.6% (n=5/32) of gastroenteritis-related deaths, respectively. Nyanga and Mitchells Plain recorded 11.5% (n= 22/192) and 9.9% (n=19/192) of respiratory infection-related deaths, respectively. Despite infections being diagnosed as cause of death, microbial analysis was only requested in 22.9% (n= 66/288) and histology was only performed in 14.9% (n= 43/288) of the cases. Where microbial analyses were requested, Staphylococcus aureus bacteria was the most common organism found, followed by Cytomegalovirus. However, due to the small numbers of microbial analyses, geographical hotspots could not be identified at the pathogen level. There is therefore a need to adopt a standard protocol for the investigation of SUDI to optimise the translation of mortality data into targeted public health interventions. The promotion of awareness in at-risk areas should be harnessed in a local context to develop preventive strategies and ultimately reduce infant death.